Author and institution citation analysis of the lean literature. (24th April 2019) - Francis, Mark; Thomas, Andrew; Fisher, Ron; Mason-Jones, Rachel
The lean paradigm is now firmly established within the field of operations and SCM. However, even though a large number of narrative reviews exist on this topical body of material, no citation analysis (CA) has yet been conducted. This paper presents the first CA of the lean literature, and also represents the most extensive known CA study within the wider field. It uses ten search phrases over a source population of over 15, 000 Google Scholar publications. These are filtered into a dataset of the 241 most highly cited publications on lean that account for an aggregated total of 98, 829 citations. The research reveals a surprising degree of influence of academics within the supposedly a theoretical lean literature. US institutions dominate, with MIT being the most influential. Both practitioners and management consultants almost exclusively co-authoring with their own type. Japan has the second largest number of management consultant authors after the USA.